If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6-(2x+7)=-2(x+6)+1
We move all terms to the left:
-6-(2x+7)-(-2(x+6)+1)=0
We get rid of parentheses
-2x-(-2(x+6)+1)-7-6=0
We calculate terms in parentheses: -(-2(x+6)+1), so:We add all the numbers together, and all the variables
-2(x+6)+1
We multiply parentheses
-2x-12+1
We add all the numbers together, and all the variables
-2x-11
Back to the equation:
-(-2x-11)
-2x-(-2x-11)-13=0
We get rid of parentheses
-2x+2x+11-13=0
We add all the numbers together, and all the variables
-2!=0
There is no solution for this equation
| (1/3x)+4=x-2 | | 4+4x=-x+59 | | 8+6x=4+2+30 | | 13x+12=7x+60 | | 5y/4-2/4=3 | | 9w-27=20 | | (4/x)+5=(3/2x)+(31/6) | | 3x+5x+4x=54 | | -9(-4+n)=-54 | | 7x+1-7=15 | | x+(.05)(x)=210000 | | 2(x+2)+3×=2(x+1)+1 | | -5x+9=x-33 | | 3/x+4+2/x-5=18/(x+4)(x-5) | | 3x-12.94=2x+12.05 | | 3x+10)-5x=6x-50 | | x-(.05)(x)=210000 | | 3(m-5)+5=0 | | 20y-8=12 | | 3(2x+4)-7=47 | | 3x+5=2x^2-3x | | 4x-2(3x+8)=5(x-3)+13 | | 5(n–7)=2(n+14) | | -2x+8=6x+40 | | 3m-15+5=0 | | (3/x)+2=(3/2x)+(17/8) | | F(1)=7x^2-3x+1 | | -5/8x=1/3 | | (3x+10)-5x=6- | | 4x+12=29 | | 2/x+1+2=8/x+1 | | -5y+6=15 |